IL-6-mediated MHC class II induction on RIN-5AH insulinoma cells by IFN-γ occurs via the G-protein pathway - S. Vassiliadis; G. K. Papadopoulos (Mediators of Inflammation)
Major histocompatibility complex (MHC) class II antigen expression has been implicated in the pathogenesis of autoimmune type 1 diabetes. In this study we examined the role of various cytoldnes that may induce MHC class II surface antigen expression, using the rat insulinoma line RIN-5AH as a pertinent model system. As in another study, the ability of IFN-γ to amplify MHC class II antigen expression 4-fold is demonstrated. At the same time we noted a 5-fold increase of these histocompatibility antigens by IL-6. Signal transduction analysis reveals that IL-6-induced MHC class II expression is specifically mediated by the G-protein system (activation of p21ras by IL-6) since mevalonic acid lactone (a Gprotein inhibitor) abolishes the action of IL-6. In contrast, IFN-γ, which does not activate p21ras, is not inhibited by protein kinase C (PKC) inhibitors but by those of the G-protein pathway. This finding raises the possibility that IFN-γ induces RIN cells to secrete IL-6 (as shown previously, as well as in this paper) which, in turn, increases class II antigen expression via the G-protein pathway. This action may be unique to IL-6 or in synergy with IFN-γ. Other cytokines such as IL-1α and β, and TNF-α induce a smaller increase in MHC class II antigens on RIN cells, and appear to activate both the G-protein and the PKC signal transduction pathways to varying degrees. Therefore, injury of pancreatic β-cells and possible induction of autoimmune type 1 diabetes via various cytokines may be caused by IL-6 or IFN-γ, or by their ability to induce MHC class II antigen upregulation.